The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1080/02642060902822083
|View full text |Cite
|
Sign up to set email alerts
|

Whiteness, ethnic minorities and advertising in travel brochures

Abstract: Whiteness theory is used in this paper as an additional way to analyse ethnic minority portrayal in advertising, specifically, the extent to which images of ethnic minorities are dominated by whiteness in travel brochures. A sample of 37 brochures are examined from British tour operators. Culture-based differences in advertising are discussed with a specific focus on how advertising constructs the image of ethnic minorities of peoples of South Asian, Afro-Caribbean and Mixed Race as tourists, workers and local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 49 publications
(57 reference statements)
1
11
0
Order By: Relevance
“…This association exists within a social context where fast food is connected to lower levels of cultural capital (Johnston and Baumann ), and it is much less frequently consumed by people from higher socioeconomic status groups (Kim and Leigh ). Regarding health food commercials, this finding corroborates some of the more specific findings regarding stereotypical corporeality of African Americans in earlier content analysis work (Burton and Klemm ; Millard and Grant ; Plous and Neptune ). Bristol et al () observe an emphasis on Black bodies in advertising and interpret this emphasis as part of a schematic White/brains versus Black/brawn dichotomy in popular culture.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This association exists within a social context where fast food is connected to lower levels of cultural capital (Johnston and Baumann ), and it is much less frequently consumed by people from higher socioeconomic status groups (Kim and Leigh ). Regarding health food commercials, this finding corroborates some of the more specific findings regarding stereotypical corporeality of African Americans in earlier content analysis work (Burton and Klemm ; Millard and Grant ; Plous and Neptune ). Bristol et al () observe an emphasis on Black bodies in advertising and interpret this emphasis as part of a schematic White/brains versus Black/brawn dichotomy in popular culture.…”
Section: Discussionsupporting
confidence: 85%
“…Unlike Asians, the range of roles Blacks play is slightly broader and includes business people (Maestro and Stern ), technicians (Pake and Shah ), and athletes (Burton and Klemm ; Pake and Shah ). They are widely featured in ads for finance/insurance, automobiles, travel (Bowen and Schmid ), and food (Bang and Reece ; Wilkes and Valencia ).…”
Section: Racial Representations In Canadian Media and In Us Advertimentioning
confidence: 99%
See 1 more Smart Citation
“…These images are not just about displaying products and attractions; they also include representations of social groups and societies (Pritchard and Morgan 2000) and rely on racial representations to attract tourists to specific locations. Consequently, if multiple studies (Alderman 2013; Burton and Klemm 2011) have found that marginalized populations are not well represented in travel brochures, how are tourism marketers planning to invite these fast-growing markets of tourists to their destinations? Whether or not the exclusion of underrepresented populations is purposeful, it alienates underrepresented populations and sends a message that they are not welcome.…”
Section: Discussionmentioning
confidence: 99%
“…In many other non-White countries, ranging from Mexico and Kenya to Sri Lanka and Fiji, long-standing discourses that have exoticized the country and presented its inhabitants as subservient by nature have fueled White tourism. Even today, travel brochures featuring Global South countries are dominated by images of Whiteness-Whites as guests and managerswhile non-White men and women feature mostly as staff serving or entertaining White guests (for instance Burton & Klemm 2011). The Raffles Hotel in Singapore and other well-known hotels where colonial elites socialized have increasingly been presented by scholars as White spaces (for example Goh 2010;Peleggi 2012;Sarmento & Linehan 2019).…”
Section: New Westmentioning
confidence: 99%